2022
DOI: 10.1088/1361-6501/ac7bd7
|View full text |Cite
|
Sign up to set email alerts
|

An all-sapphire fiber temperature sensor for high-temperature measurement

Abstract: An all-sapphire high-temperature optical fiber sensor with an extrinsic Fabry-Perot interferometer (EFPI) structure is proposed and experimentally demonstrated. The EFPI structure of the sensor is composed of a sapphire ferrule with a sapphire fiber and a polished solid sapphire crystal rod. The first reflection occurs on the left end of the sapphire ferrule, and the second reflection occurs on the right end of the sapphire rod, forming double-beam interference. The interference signal is picked up by the sapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Jiang's group [11] conducted a series of studies on sapphire fiber optic sensors, which resulted in the development of an all-sapphire fiber optic temperature sensor [12]. This sensor is packaged in an all-sapphire structure, as shown in Figure 9, which effectively eliminates the mismatch in the coefficient of thermal expansion of the material under high-temperature conditions.…”
Section: Point Temperature Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang's group [11] conducted a series of studies on sapphire fiber optic sensors, which resulted in the development of an all-sapphire fiber optic temperature sensor [12]. This sensor is packaged in an all-sapphire structure, as shown in Figure 9, which effectively eliminates the mismatch in the coefficient of thermal expansion of the material under high-temperature conditions.…”
Section: Point Temperature Sensormentioning
confidence: 99%
“…The device operated for two years from 150°C to 500°C and exhibited no failures or significant wavelength drift. All-sapphire fiber optic temperature sensor [12].…”
Section: Quasi-distributed Temperature Sensormentioning
confidence: 99%
“…The widely used K-type thermocouple has an upper limit of temperature measurement up to 1500 K, while specialized thermocouples can extend this upper limit to 3000 K. Another contact-based temperature measurement method suitable for high-temperature environments is the blackbody optical fiber temperature measurement. This approach involves embedding a blackbody into the area under measurement and utilizing optical fibers to capture the emitted radiation signal from the blackbody [15,16] proposed an allsapphire high-temperature optical fiber sensor, which can be fully qualified for long-term high-temperature measurements above 1000-1500 degrees. However, due to the melting point of optical fibers, the upper limit of temperature measurement for most studies using blackbody optical fiber thermometers is 2200 K.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a vibration sensors can be also based on optical principles. Cui et al described an all-sapphire high-temperature optical fiber sensor [ 11 ]. Additionally, Cui et al reported on a sapphire fiber high-temperature vibration sensor capable of measuring temperatures up to 1500 °C [ 12 ].…”
Section: Introductionmentioning
confidence: 99%